2005
DOI: 10.1097/01.sap.0000189662.77636.29
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis of the Palmar Digital Veins

Abstract: Our experience in 6 cases of thrombosis of the palmar digital veins is presented and an additional 20 from the world literature are reviewed. All our patients were female and suffered from a tender, bluish nodule on the palmar aspect of a digit at or distally to the proximal interphalangeal joint. In the first 2 cases, the diagnosis was confirmed on histology following excision. Four of the 6 cases were managed conservatively with a favorable outcome. All possible etiological factors were examined. Four of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Histopathological examination of digital vein thrombosis shows dilated vascular spaces, with thin-walled channels characterized by partial thrombosis and organization. In contrast to a partially thrombosed hemangioma, which may have a similar appearance, new vessels do form within the original vessel wall at the level of the thrombotic core2. Thrombus of the vein will either obliterate completely or recanalize.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Histopathological examination of digital vein thrombosis shows dilated vascular spaces, with thin-walled channels characterized by partial thrombosis and organization. In contrast to a partially thrombosed hemangioma, which may have a similar appearance, new vessels do form within the original vessel wall at the level of the thrombotic core2. Thrombus of the vein will either obliterate completely or recanalize.…”
Section: Discussionmentioning
confidence: 96%
“…It has been suggested that to distinguish between a thrombus and a hemangioma or varix of a digital vein, a tourniquet test may be of benefit. Applying a small tourniquet at the base of the involved finger will result in engorgement of the non-thrombosed varix or hemangioma2. But the palmar digital thrombotic nodules are less pronounced after prolonged raising of the arm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its first description by Jadassohn in 1936, only 37 cases have been reported in the literature. [ 1 2 ] It presents as spontaneous painful nodules on the palmar aspect of the digits, found at or near the level of the proximal interphalangeal joints, but can also be located over the middle or distal interphalangeal joints. [ 2 ] The exact etiopathogenesis of palmar digital vein thrombosis is unclear.…”
mentioning
confidence: 99%
“…Multiple factors have been speculated including the anatomy of these veins, formation of varices, intraluminal stasis of blood flow caused by flexion of the fingers and possibly by wearing rings, and endothelial injury owing to the superficial location of the digital veins getting traumatized while doing manual work. [ 1 ] The role of hypercoagulability in digital venous thrombosis is not known. Though there are a few reports of its association with conditions having hypercoagulability such as antiphospholipid antibodies, concomitant deep vein thrombosis, oral contraceptive pills, and coronavirus disease 2019 (COVID-19) infection, the majority of cases have occurred spontaneously with no underlying coagulation disorder.…”
mentioning
confidence: 99%